Amplifying the Encounters of Young Black Children with Anti-Black Racism: An Exploration of Parents’ and Early Childhood Educators’ Perspectives on Early Learning and Child Care Environments - Pimentel, Milena; McIsaac, Jessie-Lee; Watson, Crystal; Stirling-Cameron, Emma; Hickens, Nicholas; Hamilton-Hinch, Barb (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2023)
There is ongoing attention to equity and inclusion in early learning but a paucity of stories on diverse experiences. This study sought to understand the experiences of Black children in Nova Scotian early learning and child care environments through the perspectives of their parents and early childhood educators (ECEs) working in African Nova Scotian (ANS) communities or with Black children in Nova Scotia, Canada. Following in-depth interviews with parents and ECEs (n=15) three interrelated themes were identified using reflexive thematic analysis: anti-Black approach to curriculum; inaction on racism, social justice, and equity; and precluding Black children from culturally safe environments. The results highlight critical issues of racism in early learning environments and the importance of building culturally safe environments for young Black children and their families.